The Work of Postcolonial Game Studies in the Play of Culture - Murray, Soraya (Open Library of Humanities, 2018)
This article considers larger methodological questions of what political work is undertaken when scholars engage in postcolonial critiques of video games within academic intellectual frameworks. What is postcolonial game studies, and what is its purpose, within the context of larger issues of inclusion, representation, diversity, and the challenging of hegemonic power structures? After surveying some of the key literature in postcolonial game studies, the author provides critical frameworks for understanding the means by which these approaches have largely been excluded from video game studies, and their crucial function in operating against the grain of profit and innovation-driven discourses in games. This work is the extension of a larger discussion of inclusion, diversity, and tolerance discourse within the liberal academy, and particularly the functions of postcolonial, postmodern and other critical cultural scholarly interventions. In this article, the author argues for a postcolonial approach to game studies, but one that refuses to be reduced to an institutional cultural labor of due diligence, or according to Slavoj Žižek’s term, a ‘culturalization of politics’. Through the work of Stuart Hall and Sara Ahmed on intellectual diversity work within the context of large systems and academic institutions, this article asserts that the perception that critical theorizations (like postcolonial game studies) exert pressure on efficiency and innovation is greatly outweighed by the rich toolkits they bring to video games as maturing cultural forms.
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (International library of visual culture ; 27, 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Landscapes of Empire in Metal Gear Solid V The Phantom Pain - Murray, Soraya (Critical Inquiry, 2018)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé